VALUASI EKONOMI LIMBAH IKAN WADUK CIRATA MENJADI PRODUK TEPUNG IKAN - Achmad Rizal; Asep AH. Suryana; Asep Sahidin (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2019)
Mass mortality of fish in the Citarum River serial reservoir, including the Cirata reservoir has grown up to be a crucial issue for the fishing community in West Java. Fish waste due to mass death of fish in Cirata reservoir is quite high. In the context of fish mass death becomes a waste, the economic opportunity to develop fish waste into fish meal is of monetary value in terms of the availability of raw materials, nutritional composition, and marketing. In other words, the opportunity to increase fish waste into fish meal in the Cirata reservoir is fairly potential. If this happens, fish meal business has a great opportunity to enhance. Economically, economic valuation results show that: Firstly, fish meal business offers the opportunity to be developed because there is enough raw material available. Secondly, from economic analysis shows that this business is feasible, so that it has economic opportunities, this profitable opportunity will increase, if there is a mass death of fish, because production costs decrease, in this case fish prices decline. Third, the total cost required to build a fish meal home industry is Rp. 110,150,000, - with details of the initial investment costs of Rp. 63,500,000 and operational expenditure (operational costs) of 46,650,000. Finally, the economic value for the feasibility of fish flour shows that the business is feasible where BC ratio is 1.33, ROI is 6.39% and Pay Back Period is 15.63 months.Kematian massal ikan di waduk serial Sungai Citarum, termasuk di Waduk Cirata telah menjadi isu sentral bagi masyarakat perikanan di Jawa Barat. Limbah ikan akibat kematian massal ikan di Waduk Cirata cukup tinggi. Pada konteks kematian massal ikan sehingga menjadi limbah, peluang ekonomi pengembangan limbah ikan menjadi tepung ikan cukup bernilai ekonomis ditinjau dari aspek ketersediaan bahan baku, komposisi nutrisi, dan pemasaran. Dengan kata lain, peluang untuk meningkatkan limbah ikan menjadi tepung ikan di Waduk Cirata cukup potensial. Jika ini terjadi, usaha tepung ikan, memiliki peluang besar untuk berkembang. Secara ekonomi, hasil valuasi ekonomi menunjukkan bahwa: Pertama, Usaha tepung ikan mempunyai potensi untuk dikembangkan karena cukup tersedia bahan baku. Kedua, dari analisa ekonomi menunjukkan bahwa usaha ini layak (feasible), sehingga mempunyai peluang yang ekonomis, peluang ekonomi ini akan meningkat, jika terjadi kematian massal ikan, karena biaya produksi menurun, dalam hal ini harga ikan mengalami penurunan. Ketiga,Total biaya yang dibutuhkan untuk membangun home industri tepung ikan sebesar Rp. 110.150.000,-, dengan rincian biaya investasi awal sebesar Rp 63.500.000 dan biaya rutin sebesar 46.650.000,-. Keempat,Perhitungan valuasi ekonomi untuk kelayakan tepung ikan menunjukkan bahwa usaha tersebut adalah layak dimana BC Ratio sebesar 1,33, ROI sebesar 6,39 % dan dan pay back periode selama15,63 bulan.